Psychological studies of the motivational-semantic sphere in patients with diabetes mellitus - Буровська, І. (Київський національний університет імені Тараса Шевченка, 2018)
The article is devoted to the study of the motivational and semantic sphere for patients with diabetes mellitus. Description of the patients’ main directions of the psychological features are distinguished. This study aims to explorer the formation of a hierarchical system of values, attitudes, experiences and motives of this category of patients. Different approaches in the study of this problem were noted, which point to the great possibilities of prevention in the process of rehabilitation in a given subject. The leading role of psychosocial factors of impairment of their mental adaptation and quality of life in patients with diabetes mellitus is determined. Conducting theoretical analysis of modern psychological studies of the motivational and semantic sphere in patients with diabetes makes it possible to identify and analyze the main directions of rehabilitation of this category of persons, to outline the main motivational components of the disease and their relationship with the semantic sphere of each particular person. The peculiarities of the motivational and semantic sphere of persons with diabetes mellitus are described. The relationship between the motivational and intellectual sphere of personality and its influence on the formation of motives are considered. The importance of life-building and the desire to adapt to a particular way of life, to increase its qualitative characteristics and social significance, to take into account the psychological characteristics of patients, are outlined. A detailed examination of the two structural components of this study (which is one of the key tasks of this topic) allows us to more closely combine them into a single entity that forms the life-orienting purposes of patients with diabetes, and draws attention to the dynamics of motivational processes that occur in individuals during the period the course of the disease and the possibility of correction of these processes. The prospects of further researches which consist in formation and modeling of holistic construct of motivational–semantic sphere in patients with diabetes mellitus are outlined.

Виокремлено головні напрями дослідження психологічних особливостей осіб, хворих на цукровий діабет. Проведено те- оретичний аналіз сучасних психологічних досліджень мотиваційно-смислової сфери у хворих на цукровий діабет. Описано особливості мотиваційно-смислової сфери осіб, хворих на цукровий діабет. Окреслено перспективи подальших розвідок.
Психологічні дослідження мотиваційно-смислової сфери у хворих на цукровий діабет
Keywords: психологічні дослідження; мотиваційно-смислова сфера; хвороба; цукровий діабет; psychological research; motivational-semantic sphere; illness; diabetes mellitus